Preparation of highly stable and recyclable Au/electroactive polyamide composite catalyst for nitrophenol reduction. (20th January 2021) - Lai, Guan-Hui; Huang, Bi-Sheng; Yang, Ta-I; Tsai, Mei-Hui; Chou, Yi-Chen
Abstract: This article presents the first successful application of an Au/electroactive polyamide (EPA) composite as a catalyst for the reduction of nitrophenol (NP) to aminophenol (AP). The EPA was synthesized by an oxidative coupling reaction, and the in situ chemical oxidation of the reduced form of the soluble EPA in N-methyl-2-pyrrolidone was monitored by UV–vis spectroscopy. Moreover, the electroactivity of the EPA was evaluated by electrochemical cyclic voltammetry studies. The amino functional groups of the EPA were used to anchor Au nanoparticles to form an Au/EPA composite. Characterization of the Au/EPA composite was performed by field-emission scanning electron microscopy, field-emission transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. The Au/EPA composite showed an excellent performance for the reduction of NP to AP, and a conversion higher than 95% was achieved after 180 days or 30 cycles of reuse. Graphical abstract: Image 1 Highlights: First application of Au/electroactive polyamide (EPA) composite as a catalyst. Amino functional groups of EPA can act as substrate to anchor Au nanoparticles. Composite catalyst was reusable after 180 d with a conversion efficiency of >95%.